Genome size and chromosome number variation in sugarcane (Saccharum spp.) families and phenotypically contrasting Saccharum genotypes - Garcia, José María; Andrada, Aldo R.; Erazzu, Luis Ernesto; Acevedo, Alberto (Wiley, 2024)
Modern sugarcane (Saccharum spp.) cultivars originated from an intricate hybridization process, resulting in complex polyploid and aneuploid genomes. Flow cytometry (FCM), which has emerged as a precise and fast method for research on genome size in plants, has potential to unveil key aspects of sugarcane cytogenetics. In this study, FCM probes were conducted to estimate 2C DNA content in 175 Saccharum genotypes embracing phenotypically contrasting canes (commercial cultivars, energy-cane hybrids, and a Saccharum spontaneum accession) and full-sib sugarcane families. FCM-mediated DNA content estimates exhibited high accuracy in predicting chromosome numbers, offering a time-efficient alternative to classical cytogenetic procedure. Low-magnitude correlations detected between DNA content and phenotypic traits suggest that indirect selection of agronomic traits using FCM-mediated DNA content estimates may not be efficient. DNA content variation patterns in sugarcane families varied according to the crossing, and revealed transgressive variations associated with rampant aneuploidy. Altogether, the findings uncover that loss or gain of genetic material constitutes a source of high genetic variability that may substantially impact on crop breeding.